The effect of extract Kaempferia galanga rhizomes on the elimination kinetics of quinidine in rabbits - Hayati, Farida; Hakim, Lukman (Indonesian Journal of Pharmacy, 2003)
The research was aimed to observe the effect of the juice of Kaempferia galanga rhizomes on quinidine elimination kinetics in rabbits. The study on interaction of extract Kaempferia galanga rhizomes to quinidine elimination kinetic was conductedly employing a cross randomized design using male rabbits which were divided into 3 groups (6 rabbits for each group). The groups were given a single oral quinidine 30 mg/kg BW as a control group and were conferred single oral extract “kencur” 4.8 mi/kg BW each dose for 4 days prior to the treatment with quinidine. Serial blood samples(0,2 ml) were withdrawn at various interval time via the ear marginal for spectrofluorometric analysis of unchanged quinidine in blood. The concentration of quinidine was determined using a standard curve and the concentration to time data was used to determine quinidine elimination kinetics i.e. Clt and MRT. The results indicated that extract “Kencur” was found to decrease quinidine clearance 17,19% and 7,07% (P>0,05) and increase quinidine MRT198,89% and 71,70% (p>0,05).Key words : Kaempferia galanga rhizomes, quinidine, elimination